Highway engineering pavements, materials and control of quality - Nikolaides, Athanassios (CRC Press, Taylor & Francis Group, 2015)
Highway Engineering: Pavements, Materials and Control of Quality covers the basic principles of pavement management, highlights recent advancements, and details the latest industry standards and techniques in the global market. Utilizing the author's more than 30 years of teaching, researching, and consulting experience, this text focuses on the design, construction, maintenance, and management of pavements for roads and highways, and covers the main topics in highway engineering. The author integrates pavement materials, material testing for acceptability and quality assurance, asphalt mix design, flexible and rigid pavement design, construction, maintenance and strengthening procedures, quality control of production and acceptance of asphalts, pavement evaluation, asphalt plants, and pavement recycling. He also includes both European and American (ASTM and AASHTO) standards and practice, and is extensively illustrated with references, tables, graphs, charts, and photographs.